A Comprehensive Review of Open Birth Intervals: Implications for Maternal and Child Health, and Demographic Trends - Latif, Abdul (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The interval between successive births, known as the birth interval, plays a crucial role in determining maternal and child health outcomes and has significant implications for demographic trends. This review explores the concept of open birth intervals, where births are intentionally spaced without permanent contraception, highlighting their impact on health and population dynamics. Short birth intervals are linked to adverse health outcomes such as low birth weight and preterm birth due to insufficient recovery time between pregnancies. Conversely, longer birth intervals are associated with improved health outcomes, including reduced maternal and infant mortality rates, and lower fertility rates, influencing overall population growth. This review also addresses the determinants of open birth intervals, including socioeconomic status, cultural and religious beliefs, and access to reproductive healthcare services. It emphasizes the importance of comprehensive strategies for family planning, such as improving access to services, community-based education, and integrating family planning with healthcare systems. The findings underscore the need for targeted interventions and policies to support informed birth spacing decisions and achieve sustainable population growth.